Features of the Humoral Immune Response in School-age Children with Early-Onset Bronchial Asthma Depending on Acetylation Polymorphism - U.I. Marusyk (Zaslavsky O.Yu., 2015)
The objective of the work was to study the individual indicators of the humoral immune system in school-age children with early-onset bronchial asthma (BA), considering acetylation phenotypes to improve treatment outcomes. There has been carried out a comprehensive examination of 34 school-age children with early-onset BA (disease first manifested at an early age). Depending on the course of the disease, patients were divided into two clinical groups. The first clinical group included 16 patients with slow acetylation (average content of acetylated sulfadimine in urine was less than 75.0 %). The second clinical group consisted of 18 pupils with fast acetylation (average level of acetylated sulfadimine in urine was over 75.0 %). All children underwent immunological blood test of II-III levels. The studies found that slow acetylation in patients with early-onset asthma increases the risk of reduction in the amount of interleukin-8 in blood serum < 5.3 pg/ml with odds ratio (OR) 4.5 (95% confident interval (CI): 2.3-8.9), as well as the risk of higher concentration of IL-4 more than 4.0 pg/ml (OR = 1.9) that is associated with atopic inflammation of the body and allows you to personalize treatment tactics in these patients.